2007
DOI: 10.4049/jimmunol.179.5.3171
|View full text |Cite
|
Sign up to set email alerts
|

Association of TLR4 Polymorphisms with Symptomatic Respiratory Syncytial Virus Infection in High-Risk Infants and Young Children

Abstract: Respiratory syncytial virus (RSV) is a leading cause of infant mortality worldwide. Although anti-RSV Ab prophylaxis has greatly reduced infant mortality in the United States, there is currently no vaccine or effective antiviral therapy. RSV fusion (F) protein activates cells through TLR4. Two single nucleotide polymorphisms (SNPs) encoding Asp299Gly and Thr399Ile substitutions in the TLR4 ectodomain were previously associated with TLR4 hyporesponsiveness and increased susceptibility to bacterial infection. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
140
2
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(153 citation statements)
references
References 56 publications
9
140
2
2
Order By: Relevance
“…[5][6][7] Because we could not demonstrate such a difference for dengue, the correlation between the TLR4 polymorphism and RSV infection is likely to be virus specific. Interestingly, our screening of TLR4 polymorphisms showed that the distribution of the TLR4 polymorphism has a high frequency of cosegregated 299/399 in all analyzed groups.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…[5][6][7] Because we could not demonstrate such a difference for dengue, the correlation between the TLR4 polymorphism and RSV infection is likely to be virus specific. Interestingly, our screening of TLR4 polymorphisms showed that the distribution of the TLR4 polymorphism has a high frequency of cosegregated 299/399 in all analyzed groups.…”
mentioning
confidence: 86%
“…3 , 4 Children who have the Toll-like receptor 4 (TLR4) polymorphisms Asp299Gly and Thr399Ile were more susceptible to respiratory syncytial virus (RSV), a flavivirus similar to dengue virus. [5][6][7] Therefore, we assessed in children with DHF to see whether these TLR4 polymorphisms influenced susceptibility to and severity of dengue virus infections.…”
mentioning
confidence: 99%
“…Charge variation at a single residue can alter the response to lipid IV A stimulation. Single nucleotide polymorphisms at TLR4 residues 299 and 399 reportedly decrease the proinflammatory response to LPS stimulation (20). Because these residues do not directly affect recep-tor dimerization (supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous genetic studies have demonstrated a significant association between the inherited polymorphisms in several immunological and surfactant protein genes and the incidence of severe viral infection and level of infection-related morbidity among preterm infants [50,51]. Also, pre-existing impairments in lung function have also been attributed to increased susceptibility to severe viral infection and infection-related morbidity among preterm infants, particularly during early life [5254].…”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%